Nature and Scripture in the Abrahamic religions / Up to 1700 - Meer, Jitse M. van der; Mandelbrote, Scott (Brill's series in church history 1572-4107, 2008)
Evaluates the influences between scriptural exegesis and hermeneutics and the practices of interpretation in natural philosophy and natural sciences. This work aims to provide a historical context for renewed reflection on the role of the hermeneutics of scripture in the development of theological doctrines that interact with the natural sciences